ANALISIS PERENCANAAN TAHUNAN KESEHATAN SUB DINAS PENCEGAHAN DAN PEMBERANTASAN PENYAKIT DINAS KESEHATAN KOTA DEPOK TAHUN 2002 - Syafrawati Syafrawati (Jurnal Kesehatan Masyarakat Andalas, 2006)
Planning is the important function of management. An ideal health planning is planning that create base on fact and condition of teritory area. The goal of this research is to analyse annuall health planning in Sub Dinas Pencegahan dan Pemberantasan Penyakit Dinas Kesehatan Kota Depok on the year of 2002. The research is descriptive study with qualitative data. Data collected with deep interview and document observation. The result is planning process need to be improve in quality ang quantity of planner, fund for making ideal planning, facilites and writing procedur. Situation analysis does not use health determination, problem priority use mathematic methode and intervention comes from central government. The form of POA (Plan of Action ) are not specific describe the need of teritory area.